Desempenho de movimentos cíclicos e discretos realizados em tarefa de Fitts simulada em computador - Balio, Tiago Cesar; Dascal, Juliana Bayeux; Marques, Inara; Rodrigues, Sérgio Tosi [UNESP]; Okazaki, Victor Hugo Alves (My University, 2013)
Performance of cyclical and discrete movements executed in Fitts’ task simulated by computer Abstract This study compared the performance of cyclical and discrete movements in Fitts’ task simulated by a computer. Twenty male adults, between 25 and 30 years old, participated as volunteers in the study. The software Discrete Aiming Task (v.2.0) simulated the Fitts’ task, in the discrete and cyclical conditions, and provided the movement time (TM). It was manipulated 4 target widths and 3 distances between the targets to provide index of difficulties (ID) from 1 to 6 bits. The ANOVA TWO WAY, 3 (Conditions) x 6 (ID), with repeated measures in the last factor, compared the TM in the different conditions. Regression analysis verified the relationship between TM x ID. There were no significant differences between the conditions; the virtual environment and the mouse were used to explain such results. All movement conditions showed a straight relationship between TM x ID with R²>0.990. Therefore, Fitts’ law showed to be consistent, independently of the movement strategy performed.

O presente estudo comparou o desempenho de movimentos cíclicos e discretos em tarefa de Fitts simulada em computador. Participaram do estudo 20 adultos com idade entre 25 e 30 anos. O software Discrete Aiming Task (v. 2.0) simulou a tarefa de Fitts nas condições discreta e cíclica, fornecendo o tempo de movimento (TM). Foram manipuladas 4 tamanhos de alvos e 3 distâncias entre os alvos para fornecer índices de dificuldade (ID) de 1 até 6 bits. A ANOVA TWO WAY, 3 (Condições) x 6 (ID), com medidas repetidas no último fator, comparou o TM nas diferentes condições. A análise de regressão linear verificou a relação TM x ID. Não houve diferença entre as condições de movimento; o ambiente virtual e o uso do mouse foram utilizados para explicar tais resultados. Todas as condições de movimento apresentaram uma relação TM x ID com R²>0,990. Portanto, a lei de Fitts demonstrou robustez, independentemente do tipo de movimento realizado.
Keywords: Fitts`Law; Discrete movement; Cyclical movement; Speed-accuracy tradeoff; Motor control; Lei de Fitts; Movimentos discreto; Movimento cíclico; Relação velocidade-precisão; Controle motor